The Relationship Of Limb Muscle Strength To Wrestling Athlete's Kicking Ability Solok District - Bismi Fornandes; Deffri Anggara (Hanoman Journal: Physical Education and Sport, 2021)
The problem in this study originated from observations the authors met in the field, it can be seen that the Solok Regency wrestlers always fail in the opportunity to perform the slamming technique against their opponents. This is thought to be due to weak leg muscle strength. This type of research is correlational. To obtain data on leg muscle strength, the leg dynamometer test and the ability to throw a kayak were used with a dummy doll. The data obtained were analyzed by simple product moment correlation. Based on the data analysis, it was found that there was a significant relationship between leg muscle strength and the ability to throw a ball at the wrestling athlete in Solok Regency, where rcount (0.93) rtab (0.468) at a significant level (0.05). Leg muscle strength can determine the success of the throwing technique in wrestling.